2021
DOI: 10.17957/ijab/15.1828
|View full text |Cite
|
Sign up to set email alerts
|

Co-Application of Farmyard Manure and Gypsum Improves Yield and Quality of Peanut (Arachis hypogaea) under Rainfed Conditions

Abstract: Peanut (Arachis hypogaea L.) is the common cash crop of the rainfed areas. Appropriate management practices are very important to get better yield of peanut in sandy loam soil. A field study was carried out during the growing seasons of 2018 and 2019 to evaluate the effect of poultry manure (PM) (37.1 t ha-1), farmyard manure (FYM) (49.4 t ha-1), gypsum (GYP) (2.5 t ha-1), liquid humic acid (HA) (49.4 L ha-1) and co-application of GYP (1.2 t ha-1) and FYM (24.7 t ha-1) on peanut yield, quality and soil physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This is in accordance with Sulaiman and Mohammed 24 , who stated that application organic and NPK fertilizers increased the sweetness level of grapes. Likewise, Latif et al 13 reported that, the combined application of gypsum and compost increased pod yield by 67 and 65% during 2018 and 2019, respectively compared to the controls. Crude protein of 21% and oil content of 9.0% also increased substantially in the combined application.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with Sulaiman and Mohammed 24 , who stated that application organic and NPK fertilizers increased the sweetness level of grapes. Likewise, Latif et al 13 reported that, the combined application of gypsum and compost increased pod yield by 67 and 65% during 2018 and 2019, respectively compared to the controls. Crude protein of 21% and oil content of 9.0% also increased substantially in the combined application.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the report by El-Negar and Mohamed 12 , cow manure contains the mineral N. This process depends on the type of manure and its nutrient content, soil temperature and humidity among other factors. The chicken manure contains N (6.99-7.78%), P (0.89-099%), K (4.88-5.70%), organic matter (37.80-38.09%), bulk density (0.39-0.86%) and total porosity (31.00-60.40%), while the mineral nutrient content of compost (agricultural waste) contains N (0.51-0.53%), P (0.21-0.23%) and K (0.60-0.65%) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Cow manure includes the mineral N [20]. In contrast to compost (agricultural waste), which has N, P, and K content of 0.51-0.53%, 0.21-0.23%, and 0.60-0.65%, respectively, as its mineral nutrients, chicken manure contains 6.99-7.78% N, 0.89-099% P, 4.88-5.70% K, 37.80-38.09% organic matter, 0.39-0.86% bulk density, and 31.00-60.40% total porosity [21]. Based on the report of Nguyen et al [22], adding compost + mulch or compost alone can increase available water and air exchange tomato cultivation, whereas Abouziena and Haggag [23] reported that straw mulch was consistent in controlling weeds and had an effect on soil chemicals properties and had a low effect on apple fruit yield.…”
Section: Introductionmentioning
confidence: 99%